Periferia e centro comunitário: experiências do habitar e a vida de uma organização comunitária - Paulo Sérgio Lima da Silva; Carmem Izabel Rodrigues (Ciências Sociais Unisinos)
This article aims to reflect on the way the experiences of residents on the outskirts of a city give life to grassroots organizations such as a community center and influence the performance of these entities. In this sense, the ideas presented here make use of, and try to interpret, with another focus, data collected in a case study conducted at the São Paulo Community Center in Icoaraci, which is an administrative district of the city of Belém, Pará State. The theoretical and methodological framework is based on the analysis of phenomena such as socio-spatial segregation, urban exploitation, family networks, moral region and “crime speeches” in a space in (and from) the periphery. Thus, the entity and its actions are perceived here as a mirror of life on the streets, as they are influenced both by local needs (in terms of infrastructure and other services) and by the existence of an intense sociability that gathers residents of the peripheral neighborhood of Campina Icoaraci within the Community Center.